2016
DOI: 10.1007/s10900-016-0207-5
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Intervention to Improve the Quality of Lunchboxes Among Mexican School Children

Abstract: In Mexico, the type of foods included in the lunchboxes of school children are unhealthy. The aim of this study was to evaluate the effects of an intervention program to improve the quality of the foods in the lunchboxes. Two schools were randomly selected as the intervention group (IG) and two more as the control group (CG). The evaluation was performed by comparing a food list from 3 days before and 6 months after the intervention. The components of the intervention included: exposure to posters inside and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 23 publications
0
15
0
3
Order By: Relevance
“…A description of the included studies is shown in Table 1. Of the 10 included trials, three were conducted in the U.S., [3133] three in U.K., [21, 3436] two in Australia [37, 38], one in Mexico [39] and one in Israel [40]. Eight of the studies employed cluster randomised-controlled trial designs, [21, 31, 32, 34, 3740] and two were conducted using quasi-experimental designs [24, 35]…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A description of the included studies is shown in Table 1. Of the 10 included trials, three were conducted in the U.S., [3133] three in U.K., [21, 3436] two in Australia [37, 38], one in Mexico [39] and one in Israel [40]. Eight of the studies employed cluster randomised-controlled trial designs, [21, 31, 32, 34, 3740] and two were conducted using quasi-experimental designs [24, 35]…”
Section: Resultsmentioning
confidence: 99%
“…These trials recruited samples of between 132 and 560 children with the age of participants ranging from 3 to 6 years. Of the six trials conducted in schools, [21, 31, 34, 35, 39, 40] the number of participating schools ranged from two to 89. These trials recruited samples of between 238 and 2443 students with the age of participants ranging from 4 to 14 years.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations